Kinetics of change making of a lubricant layer at friction of contact surfaces in extreme conditions - Маленко, В.І. (Proceedings of National Aviation University (archive), 2004)
А question about prognostication development impermissible types wear - grasping and jamming is considered in article. Using method separate measuring thickness lubricating, kinetics change making thicknesses lubricating layer is shown. Intercommunication and basic conformities to law change between total thickness lubricating layer and tribotehnicheskimi parameters - moment friction and work friction is set experimentally.